Indonesian Environmental Reporting Index dan Karakteristik Perusahaan - Djoko Suhardjanto; Laras Miranti (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2009)
The purpose of this study is to examine relationship between company characteristics and its environmental disclosures. Company characteristics are identified as size, leverage, profitability, and company’s operation territory. This study also investigates industry type and corporate governance provisions as control variable. Companies’ environmental disclosures are measured by using the Indonesian Environmental Reporting index developed by Suhardjanto, Tower and Brown (2007). Under proportional random sampling method, 80 Indonesian listed companies’ annual reports are selected. From the sample, there is fifty three point seventy five percent (53.75%) disclosed environmental information. Result of statistical analysis shows that profitability and industry type are as significant predictors to environmental disclosure. The implication is that the regulator should encourage companies with high profit should be more concern to report their environmental activities. In addition, manufacture companies have to have more responsibility to inform their environmental activities in annual reports than service or financial companies. Keywords: environmental disclosure, company characteristics, Indonesian Environmental Reporting (IER) index.